PENGEMBANGAN MODUL PROBLEM BASED LEARNING (PBL) BERORIENTASI GREEN CHEMISTRY UNTUK PENINGKATAN LITERASI SAINS SISWA - Fauziah, Nurul; Suryati, Suryati; Mashami, Ratna Azizah (IKIP Mataram, 2016)
The aim of this study was to determine the characteristics, the feasibility practice and the effectiveness of developed module. This study used a model of development Nieveen began preliminary stages of research, prototyping stage, summative evaluation and systematic reflection and documentation. Validation of products was conducted by expert lecturers of chemistry and expert lecturers of media with the percentage of feasibility an average of 93.6% to the category of very feasible. The practice of module testing by the chemistry teachers and students of XII MIA grade and testing of learning plan. Trial by teachers got the average percentage of the feasibility is 94.75% categorized as very practice, testing students gained average percentage of the feasibility was 95% categorized as very practice. The precentage of learning plan was 95% categorized as very practice. The effectiveness of developed module obtained an average score of N-Gain students namely 0.4 categorized as moderate. Based on the percentage of feasibility and the effectiveness level, so it can be concluded that the Problem Based Learning (PBL) module oriented green chemistry in salt hydrolysis concept to improve the scientific literacy of students were feasible, practice, and effectively used to improve the scientific literacy of students.